1986
DOI: 10.1172/jci112427
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of glucocorticosteroids. Inhibition of T cell proliferation and interleukin 2 production by hydrocortisone is reversed by leukotriene B4.

Abstract: The mechanism whereby glucocorticosteroids are immunosuppressive is unknown. One potential mechanism of action of these compounds is inhibition of arachidonic acid metabolism. We found that the inhibition of lymphocyte proliferation by hydrocortisone or dexamethasone was mimicked by nonspecific lipoxygenase inhibitors and also by a specific 5-lipoxygenase inhibitor, but not by a specific cyclooxygenase inhibitor. Mitogen-stimulated cultures of T cells produce -5 X 10-9 M leukotriene B4 (LTB4) in 24 h. This pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(30 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“…A23187 (2 uM) induced significant production of these two eicosanoids in the low-dose group. However, their levels (all in ng/mg glomerular protein) were not statistically different from respective controls (5-HETE, 12 4.4 Values reflect the mean of duplicate observations. cantly higher levels by 24 h when significant PMN infiltration was still present (3.2±0.4).…”
Section: Methodsmentioning
confidence: 76%
“…A23187 (2 uM) induced significant production of these two eicosanoids in the low-dose group. However, their levels (all in ng/mg glomerular protein) were not statistically different from respective controls (5-HETE, 12 4.4 Values reflect the mean of duplicate observations. cantly higher levels by 24 h when significant PMN infiltration was still present (3.2±0.4).…”
Section: Methodsmentioning
confidence: 76%
“…Obviously, steroid-induced cell death would interfere with the ability of the dead lymphocyte to participate in the immune response. However, it has been shown recently that steroids can interfere with the immune response by inhibiting production ofleukotriene B4 in mitogen-stimulated lymphocytes (21). Thus, interference with arachidonic acid metabolism may produce a pathway for inhibiting the immune response without causing cell death.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to these studies, other investigators have reported that lymphocytes have the capacity to synthesize 5-hydroxyeicosatetraenoic acid and leukotrienes from arachidonic acid [37,38]. However, one of these groups has not been able to confirm their initial findings [lo].…”
Section: Effects Of Monoc~te/monoclonal Lymphocytic Cell Interactionsmentioning
confidence: 96%